A methodological approach to ε-caprolactone modification of wood. (5th July 2022) - Ermeydan, Mahmut Ali; Cambazoğlu, Merve; D. Tomak, Eylem
Abstract: Due to increasing environmental awareness, in recent years the research on classical wood preservation by hazardous impregnation chemicals has been shifted to more environmentally friendly chemical modification methods with organic molecules/polymers. The chemical modification processes rely on the replacement or blockage of wood hydroxyl groups with generally hydrophobic molecules, thereby improving the dimensional stability, water repellency and biological resistance of the wood. This study investigates in situ polymerization of ε-caprolactone to form poly(ε-caprolactone) (PCL), a biodegradable polymer, which was grafted to the wood cell walls of both Scots pine ( Pinus sylvestris L.) and spruce wood ( Picea orientalis L.). Wood modification by in situ polymerization of ε-caprolactone has been studied so far in order to be an alternative modification approach to obtain improved wood properties, such as good dimensional stability and improved water resistance without reducing mechanical properties considerably. In the light of previous studies, the current work proposes a methodological approach to ε-caprolactone modification in two aspects: (i) the effect of catalyst (tin(II) 2-ethylhexanoate) amount on wood properties (i.e., swelling (S), anti-swelling efficiency (ASE), water uptake (WU), mass loss (ML)) (ii) the effect of oven or solvent curing of ε-caprolactone on wood properties (i.e., S, ASE, WU, ML, compressive strength parallel to the grain, and chemical components). By these approaches, an optimum catalyst amount was determined, and an alternative method (oven-curing) which may be more economic by enabling the re-use of the waste chemical was evaluated in comparison to the method of ε-caprolactone modification in prior publications (solvent-curing).